(untitled) (diségno, 2025)
The book I disegni di Francesco Valenti. Elementi espressivi e caratteristiche tecniche (Drawings by Francesco Valenti. Expressive Elements and Technical Characteristics), edited by Adriana Arena and scheduled for publication in 2024 as part of FrancoAngeli’s Forme del Disegno series, offers an in-depth study of the graphic works of architect and engineer Francesco Valenti, who was active from the late 19th century into the early 20th century. [read more]